(untitled) (Revista Argentina de Musicología, 2018)
The Bolivian Chiriguano are one of the few American native groups that managed to hold on to a relative autonomy throughout the colonial and early republican times, until they were finally forced to submit towards the end of the 19’h century. Colonial and republican advance operated in different ways; an important one was spearheaded by the Franciscans with the settlement of missions in Chiriguano territories from the mid 18’h century on. Once the missions were firmly rooted, the missionary project attempted not only to integrate the aborigines to the "society with enforcement" and their Christianization, but also to control their main cultural artifacts, like sound, time and space. In fact, both Europeans and Natives were well aware that "sound’’, " noise" and "silence" were a source of power and knowledge. This led to a heavyhanded policy aimed at wiping them out, something that in turn led to deep processes of change within the Chiriguano world of sounds.